ERROR ANALYSIS AND ENGLISH SYLLABUS - Khansir, Ali Akbar (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
The present article is an attempt to examine the place of English syllabus and its relationship with error analysis in English language class. In recent years, there has been a positive trend in English language courses with the focus shifting from teacher –centered to learner centered activities and in this connection, the role of error analysis as one of the theories has been associated with English language courses in teaching English in English foreign or second classes. This paper tries to trace theoretically the notion of Error Analysis and its important and validity in English language courses. The term Error Analysis gained prominence during 1960s and developed as a branch of Applied Linguistics to language teaching. It has been particularly associated with the field of linguistic analysis of language learner' errors in target language. One of the greatest contributions of Error Analysis to language teaching has been its emphasis on careful and extensive learners' errors for language syllabus in general and English in particular.